Management of Vatakantaka w.s.r to Calcaneal Spur by Agnikarma (International Journal of Ayurveda and Pharma Research, 2025)
Objectives: In today’s day to day life, prolonged hours of standing, poorly fitted and hard sole footwear, excessive walking, running and being overweight, they all are the risk factors of the calcaneal spur. There is no proper treatment in modern medicine other than surgery but Ayurveda offers a variety of treatment procedures through which patient can get relief. One of the most effective methods is Agnikarma. In Ayurvedic texts, similar signs and symptoms are found in a Vatavyadhi named Vatakantaka. Thus, Vatashamak chikitsa becomes the basis of the treatment. Materials and Methods: An attempt has been made in which 5 patients with calcaneal spur, confirmed by X-Ray having main complain of pain and tenderness in heel region were taken under study and Agnikarma were done for consecutive 3 weeks (once a week). Result: After the therapy, patient feels instant relief in the pain. Conclusion: This proves that the Agnikarma plays a very effective role in the management of calcaneal spur.